2016 25th Wireless and Optical Communication Conference (WOCC) 2016
DOI: 10.1109/wocc.2016.7506564
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of dual polarization WDM and SCM Radio over Fiber and Radio over FSO for C-RAN architecture

Abstract: In this paper, the transmission schemes for Centralized Radio Access Network Architecture (C-RAN) based on combination of two technologies -Radio over Fiber (RoF) and Radio over FSO (RoFSO) are simulated and experimentally verified. The proposed setups are optimized for Long Term Evolution (LTE) with 20 MHz bandwidth using 64 Quadrature amplitude modulation in terms of Error Vector Magnitude (EVM). At the first, the measurements of Polarization Division Multiplexing using combination of RoF a RoFSO (PDM-RoF/FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…To do so, it used mode division multiplexing scheme of two independent channels through spiral-phased HG 00 mode with vortex lens m=1 and HG 01 mode with vortex lens m=3. Simulations proved that FSO link prolongs to14 km with acceptable SNR (for channel 1= 24.11 and for channel 2= 20.54 dB) and log of BER (for channel 1= -30.584 and for channel 2 = -19.504) under clear weather conditions. Whereas in case of various atmospheric turbulences, FSO link prolongs to 1400 m in moderate fog with acceptable SNR (for channel 1=21.23 dB and for channel 2= 18.34 dB).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…To do so, it used mode division multiplexing scheme of two independent channels through spiral-phased HG 00 mode with vortex lens m=1 and HG 01 mode with vortex lens m=3. Simulations proved that FSO link prolongs to14 km with acceptable SNR (for channel 1= 24.11 and for channel 2= 20.54 dB) and log of BER (for channel 1= -30.584 and for channel 2 = -19.504) under clear weather conditions. Whereas in case of various atmospheric turbulences, FSO link prolongs to 1400 m in moderate fog with acceptable SNR (for channel 1=21.23 dB and for channel 2= 18.34 dB).…”
mentioning
confidence: 87%
“…In this case, radio over free space (Ro-FSO) technologya combination of free space and radio over fibre schemecan be useful for transporting radio carrier over free space link. Ro-FSO can be utilised by existing mobile cellular architectures in rural areas to a) distribute RF signals at high bandwidth, b) have low attenuation losses, and c) consume low power [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…FSO-SCM performance was assessed in 2009 for the transmission of CDMA signals underneath the Gamma-Gamma situation FSO channel [137]. In 2016, Petr et al combined the technique of PDM with the FSO-SCM method and showed that the system performance was improved by using PDM in terms of launch power to reach the required error vector magnitude (EVM) limit [138]. In Ref.…”
Section: Fsoc With Wdm and Scm Techniquesmentioning
confidence: 99%
“…Recent developments in Ro-FSO include experimental measurements [9][10][11] and mathematical modeling [12][13][14][15] under atmospheric turbulence and scintillation effects. To increase the capacity of Ro-FSO systems, multiplexing in the wavelength [16], intensity [17]matand polarization [18] dimensions has been demonstrated. The eigen-mode dimension has garnered significant momentum in recent years for multiplexing disparate data streams in mode division multiplexing (MDM).…”
Section: Introductionmentioning
confidence: 99%